STRATEGI GURU PENDIDIKAN AGAMA KRISTEN DALAM MENANGGULANGI DEKADENSI MORAL DI SMP NEGERI SATAP LANGIRA - Marselina T Babang; Dwi Novita Sari; Yonathan Yakup Mononimbar (SAGACITY : Journal of Theology and Christian Education, 2021)
In Christian religious education (PAK) learning must have a purpose that leads to transformation in both knowledge and faith. Pak's goal is to develop the ability of learners to obey and devotion to God and His word, expressed in daily life, both in the family, church, congregation and community. But the change and development of the times, the entry of new cultures and other factors began to erode the morale of students. The phenomenon that occurs in Satap Langira State Junior High School is the presence of students who are pregnant out of wedlock, ditching behavior, smoking in school, drinking alcoholic beverages in the school environment, which affects the emergence of immoral behavior. Therefore, PAK teachers seek strategies in teaching PAK in order to overcome existing moral decadence. The method used in this study is a method of decryptive analysis with a qualitative approach. The data analysis technique used is data trianggulation with data collection techniques, namely interviews, field observations and documentation. The result found that the pak teacher's strategy in overcoming moral decadence is to strengthen the "truth" of faith through the cultivation of noble Christian values and in line with existing moral values. In addition, the teacher is also an exemplary person who is able to give a positive influence to learners. The approach is a personal approach. A personal approach is taken when certain students experience problems both in learning and in association. Teachers also put themselves as motivators who are able to inspire students in doing many things related to association and lessons.